Depletion of tumor-associated macrophages switches the epigenetic profile of pancreatic cancer infiltrating T cells and restores their anti-tumor phenotype. (1st February 2018) - Borgoni, Simone; Iannello, Andrea; Cutrupi, Santina; Allavena, Paola; D'Incalci, Maurizio; Novelli, Francesco; Cappello, Paola
ABSTRACT: Pancreatic Ductal Adenocarcinoma (PDA) is characterized by a complex tumor microenvironment that supports its progression, aggressiveness and resistance to therapies. The delicate interplay between cancer and immune cells creates the conditions for PDA development, particularly due to the functional suppression of T cell anti-tumor effector activity. However, some of the mechanisms involved in this process are still poorly understood. In this study, we analyze whether the functional and epigenetic profile of T cells that infiltrate PDA is modulated by the microenvironment, and in particular by tumor-associated macrophages (TAMs). CD4 and CD8 T cells obtained from mice orthotopically injected with syngeneic PDA cells, and untreated or treated with Trabectedin, a cytotoxic drug that specifically targets TAMs, were sorted and analyzed by flow cytometry and characterized for their epigenetic profile. Assessment of cytokine production and the epigenetic profile of genes coding for IL10, T-bet and PD1 revealed that T cells that infiltrated PDA displayed activated Il10 promoter and repressed T-bet activity, in agreement with their regulatory phenotype (IL10 high /IFNγ low, PD1 high ). By contrast, in Trabectedin-treated mice, PDA-infiltrating T cells displayed repressed Il10 and Pdcd1 and activated T-bet promoter activity, in accordance with their anti-tumor effector phenotype (IL10 low /IFNγ high ), indicating a key role of TAMs in orchestrating functions of PDA-infiltrating T cells by modulating their epigenetic profile towards a pro-tumoral phenotype. These results suggest the targeting of TAMs as an efficient strategy to obtain an appropriate T cell anti-tumor immune response and open new potential combinations for PDA treatment.